Auditor Independence Meaningful Abstract - Novrida Qudsi Lutfillah; Yenni Mangoting; Darti Djuharni (Yayasan Rumah Peneleh, 2020)
This study purpose is to reveal the meaning of auditor independence based on auditor’s experience. Phenomenological approach was employed as a research method. Data analysis in this study used modified analysis stage of Creswell and Moustakas. Results showed that independence is defined as something ABSTRACT (A=Auditor, B=Behaviour, S=Self Concept, T=Thought, R=Risk, A=Ability, C= Competency, T=Trust). Auditor independence is affected by self concept and trust. Auditor’s behavior toward risk, whether independent or not, provides two alternatives, namely: “how to deal with it later” and “we will see about it later”. Eventually, auditor independence depends on thought, ability and competency.